Ideal Practices and Dowry System in the Muslim Communities of Nepal - Upadhyay, Chandra (Bouddhik Abhiyan (बौद्धिक अभियान), 2023)
This paper analyzes the ideal practices and the dowry system in Muslim communities in Nepal. Here, the term “ideal practices” refers to a system or set of practices that include the effectiveness of human experience and behavior, including traditions, customs, and social practices prevalent in a community. Muslim communities in Nepal follow their own way of life based on Islamic ideals. Amidst the ideal practices, the dowry system is prevalent among them. However, the system, as practiced in contemporary Muslim society, has been reported as a social and economic barrier. This paper, based on a descriptive research design and a qualitative approach, answers the question of what dowry is for Muslims, how they practice it, and why they socially discard the practice. It uses both secondary and primary data. The secondary data were collected through reviews of published books on Muslims in Nepal, and the literature available in archives and e-resources. Similarly, the primary data were collected through interviews, focus group discussions, and field observations in Morang and Sunsari districts of Nepal’s Terai. This article also uses local stories to understand the prevalence of the dowry system in the Muslim community. The analysis of various stories indicates that the dowry system is prevalent in the Muslim community due to the fanaticism of the community, superstition, greed, personal intention, social imitation, and level of perception. This research concludes that efforts such as adherence to Islamic ideals against dowry, socialization, awareness, and education can have a positive effect on controlling dowry. The paper contributes to social awareness against the dowry system among Muslims and other communities in Nepal.